Independent time markers validate 210Pb chronologies for two shallow Argentine lakes in Southern Pampas. (5th May 2017) - Córdoba, Francisco E.; Piovano, Eduardo L.; Guerra, Lucía; Mulsow, Sandor; Sylvestre, Florence; Zárate, Marcelo
Abstract: We report here the results of detailed 210 Pb analysis from two lake sediment cores collected from Lagunas Encadenadas del Oeste (LEO), located in the southern Argentinean Pampas (37°S, 62°W). Non-exponential and non-monotonic 210 Pbuns depth-profiles in the sedimentary record of these shallow lacustrine systems indicate the interaction of complex processes behind radionuclide fluxes and lake sedimentation. The chronologies and sediment accumulation rates (SAR) for the lake sediment sequences were modeled using different 210 Pb-based mathematical models. Since modeled 210 Pb ages must be validated against independent stratigraphic markers of known age, two chrono-stratigraphic markers were selected to control the upper and lowermost parts of the 210 Pb dated sediments. The younger stratigraphic marker of AD 1980 ± 2 corresponds to an uppermost organic carbon-rich mud accumulated by 1977–78 matching the most noticeable lake highstand occurred during the 20th century, registered on instrumental and paleolimnological records across the Pampean Plains. The oldest stratigraphic marker corresponds to AD 1878 ± 10 matching with a high lake productivity and wet phase related to anomalously intense rainfall and flooding events in southeastern South America for AD 1877–1878. When comparing the resulting ages to the stratigraphic markers, our results show that CRS-model (constant rate of supply) performs better than the other models. Thus, these independent chronostratigraphic markers used along the sedimentary records were critical to validate 210 Pb-derived ages and therefore to select the most appropriate model to establish the chronological framework of the recent sediments of the LEO system. The CRS-model appears to be an adequate technique for deriving ages and SAR in the LEO sedimentary record and other Pampean lacustrine systems under strong hydrological variability.